Two Rare Cases of Hepatocellular Carcinoma after Kasai Procedure for Biliary Atresia: A Recommendation for Close Follow-Up - Alicia C. Hirzel; Beatrice Madrazo; Claudia P. Rojas (Case Reports in Pathology, 2015)
The instigation of the Kasai procedure in infants who are born with biliary atresia has led to increased survival in this population for over half a century. The many complications that arise as a result of biliary atresia led to an early death for most patients. However, the Kasai procedure is not without its own impediments. Among them is the development of hepatocellular carcinoma. We present two cases of hepatocellular carcinoma, after Kasai procedure, from two different age groups, as a recommendation that these patients should be even more closely monitored. Furthermore, if they are in need of transplant, we recommend that the explanted livers be carefully examined, as the tumor may not have been diagnosed preoperatively.